Kid cat bonds, o el caso para la emisión de cat bonds contra pérdidas por el Niño - Barreda Ayllón, Alonso (2023)
We live in constant exposure to natural catastrophes. Its occurrences have taught us it is necessary to work on prevention of damages and mitigation of potential losses. Although risk management in Peru is still deficient, it is necessary to recognize there are tools that can help us protect our interests.In this article, the author seeks to explain how catastrophic bonds or CAT Bonds work, presenting them as a hedge or financial alternative to face potential losses from next occurrences of El Niño.